Effect of polyphenol-rich cranberry extracts on cariogenic biofilm properties and microbial composition of polymicrobial biofilms. (June 2019) - Philip, Nebu; Bandara, H.M.H.N.; Leishman, Shaneen J.; Walsh, Laurence J.
Highlights: Polyphenol-rich cranberry extracts disrupted cariogenic properties of saliva-derived polymicrobial biofilms. Polyphenol-rich cranberry extracts modulated a beneficial change in the microbial composition of the polymicrobial biofilms. Abstract: Objective: To investigate the effect of cranberry extracts on saliva-derived polymicrobial biofilms with regards to biofilm biomass, acidogenicity, exopolysaccharide (EPS)/microbial biovolumes, colony forming unit (CFU) counts, and the relative abundance of specific caries- and health-associated bacteria. Methods: Saliva-derived polymicrobial biofilms were grown for 96 h in a cariogenic environment and treated for 2 min every 12 h over the entire biofilm growth period with 500 μg/mL cranberry extract or vehicle control. The effect of the cranberry extract on biofilm behaviour was evaluated using different assays and its influence on key cariogenic and health-associated bacterial populations was assessed with a microarray real-time quantitative PCR method. Results: Cranberry-treated biofilms showed significant drops in biomass (38% reduction, P  <  0.001), acidogenicity (44% reduction, P  <  0.001), EPS/microbial biovolume ratios ( P  =  0.033), and CFU counts (51% reduction, P  =  0.001). Furthermore, the cranberry extracts effected a significantly lower relative abundance of caries-associated Streptococcus sobrinus (fold change 0.004, P  =  0.002) and Provotella denticola (0.002, P  <  0.001), and a significantly higher relative abundance of the health-associated Streptococcus sanguinis (fold change 90.715, P  =  0.001). Conclusions: The cranberry extract lowered biofilm biomass, acidogenicity, EPS/microbial biovolumes, CFU counts, and modulated a beneficial microbial ecological change in saliva-derived polymicrobial biofilms.